Nilai-Nilai Pendidikan Dalam Tadisi Horja Mandailing - Arianto,; Nur Maidah,; Amalian Zahra,; Khodijah Rangkuti,; Khoirunnisah Hsb,; Rahmi Wahyuni, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This paper aims to explore the educational values embedded within the horja tradition of the Mandailing community, which serves as one of the prominent expressions of local wisdom in Mandailing culture. The horja tradition refers to a form of collective work or mutual cooperation typically practiced in various social, customary, and religious activities such as weddings, funerals, public construction, and other communal events. Through a literature-based analysis drawing from various studies on Mandailing culture and educational theory, it is revealed that horja embodies several key educational values, including solidarity, cooperation, responsibility, discipline, and social concern. These values not only strengthen social bonds within the community but also hold pedagogical importance as foundations for character formation in learners. The findings indicate that preserving the educational values inherent in the horja tradition contributes significantly to reinforcing cultural identity and fostering humanistic values aligned with the aims of education